Mid-upper arm circumference in detection of weight-for-height Z-score below −3 in children aged 6–59 months. Issue 10 (5th February 2018) - Kapil, Umesh; Pandey, RM; Bansal, Rahul; Pant, Bhavana; Varshney, Amit Mohan; Yadav, Chander Prakash; Sinha, Shikha; Sareen, Neha; Sachdev, Harshpal Singh
Abstract: Objective: To evaluate the predictive ability of mid-upper arm circumference (MUAC) for detecting severe wasting (weight-for-height Z -score (WHZ) <−3) among children aged 6–59 months. Design: Cross-sectional survey. Setting: Rural Uttar Pradesh, India. Subjects: Children ( n 18 456) for whom both WHZ ( n 18 463) and MUAC were available. Results: The diagnostic test accuracy of MUAC for severe wasting was excellent (area under receiver-operating characteristic curve = 0·933). Across the lower range of MUAC cut-offs (110–120 mm), specificity was excellent (99·1–99·9 %) but sensitivity was poor (13·4–37·2 %); with higher cut-offs (140–150 mm), sensitivity increased substantially (94·9–98·8 %) but at the expense of specificity (37·6–71·9 %). The optimal MUAC cut-off to detect severe wasting was 135 mm. Although the prevalence of severe wasting was constant at 2·2 %, the burden of severe acute malnutrition, defined as either severe wasting or low MUAC, increased from 2·46 to 17·26 % with cut-offs of <115 and <135 mm, respectively. An MUAC cut-off <115 mm preferentially selected children aged ≤12 months (OR=11·8; 95 % CI 8·4, 16·6) or ≤24 months (OR=23·4; 95 % CI 12·7, 43·4) and girls (OR=2·2; 95 % CI 1·6, 3·2). Conclusions: Based on important considerations for screening and case detection in the community, modification of the current WHO definition of severe acute malnutrition may not be warranted, especially in the Indian context.